Supratentorial and pontine MRI abnormalities characterize recessive spastic ataxia of Charlevoix‐Saguenay. A comprehensive study of an Italian series. Issue 1 (21st July 2012) - Prodi, E.; Grisoli, M.; Panzeri, M.; Minati, L.; Fattori, F.; Erbetta, A.; Uziel, G.; D'Arrigo, S.; Tessa, A.; Ciano, C.; Santorelli, F. M.; Savoiardo, M.; et al.
Abstract : Background and purpose: The autosomal recessive spastic ataxia of Charlevoix‐Saguenay (ARSACS) is an early‐onset neurodegenerative disorder caused by mutations in the SACS gene. The disease, first described in Canadian families from Québec, is characterized by cerebellar ataxia, pyramidal tract involvement and peripheral neuropathy. Methods: Analysis of SACS gene allowed the identification of 14 patients with ARSACS from 13 unrelated Italian families. Clinical phenotype, gene mutations and magnetic resonance imaging (MRI) findings were analysed. Results: We found 16 novel SACS gene mutations, including a large in‐frame deletion. The age at onset was in infancy, but one patient presented the first symptoms at age 32. Progression of the disease was variable, and increased muscle tone was mostly recognized in later stages. Structural MRI showed atrophy of the superior cerebellar vermis, a bulky pons exhibiting T2‐hypointense stripes, identified as the corticospinal tract (CST), thinning of the corpus callosum and a rim of T2‐hyperintensity around the thalami in 100% of cases. The presence of iron or other paramagnetic substances was excluded. Diffusion tensor imaging (DTI) revealed grossly over‐represented transverse pontine fibres (TPF), which prevented reconstruction of the CST at this level (100% of cases). In all patients, significant microstructural alterations were found in the supratentorial white matter of forceps, cingulum and superior longitudinal fasciculus. Conclusions: Our findings further enlarge the genetic spectrum of SACS mutations and widen the study of clinical phenotype. MRI characteristics indicate that pontine changes and supratentorial abnormalities are diagnostic. The over‐representation of TPF on DTI suggests a developmental component in the pathogenesis of the disease.